Increasing the Psychological Competence of Nurses in Pediatrics: Directions, Forms, Contents - I. M. Spivak; E. G. Biryukova (Педиатрическая фармакология)
Relevance. In recent years the powers of nurses have been considerably expanded, which determines the increase of their responsibilities and the need of permanent improving of their skills.Object: determination of directions, forms and contents of training courses for increasing psychological competence of pediatric nurses in connection with their status and work experience.Methods and the object of research. The main method was a questionnaire developed by the article’s authors. 59 pediatric nurses from different regions of the Russian Federation who participated in remote educational cycles in Moscow and Yekaterinburg have been included in the survey. Nurses were divided into two groups based on their status and experience in the specialty. The group consisted of 31 respondents (average age 41,2 years). 28 respondents were Managers of nursing (average age 40,8 years).Results and conclusions. Stress management skills are more essential for nurses than for nursing managers and nursing staff with work experience of up to 10 years and over 20 years. Communication skills are relevant for nursing managers and nursing staff with experience of over 20 years. For all the nurses, situational assistance in complicated communicative situations and stress management is a priority compared to the long-term psychological support. The choice of education form (seminar, training) does not depend on the nursing staff’s status and work experience.